Cows’ and buffalo milk for cooked fresh cheese: preliminary comparison of the cheese-making efficiency and quality of griddled acid/heat-coagulated Paneer and rennet-coagulated Tosella/Schiz - Nageshvar Patel; Nicolò Amalfitano; Giovanni Bittante (Italian Journal of Animal Science)
Milk from cows and buffaloes represents the major source of dairy products worldwide. Cheese is consumed fresh, ripened, cooked, or as recipe ingredient in many different types. Using Paneer and Tosella/Schiz model cheeses as a case study of cooked cheeses, in this short communication we evaluated the cheese yield and quality of fresh cheese before and after cooking comparing the two major dairy species (cows and buffaloes). A total of 75 model cheeses (37 Paneer and 38 Tosella/Schiz) were made. Slices of all the cheeses were cooked on a griddle at 130 °C. Milk, whey, and cheese composition traits, cheese-making efficiency traits, and cooked cheese quality traits were evaluated using a mixed model that included the fixed effects of cheese type and animal species, and their interaction, and the random effects of session, animal within species, and the residual. Higher cheese yields are obtained from the buffalo milk not only because more concentrated in nutrients, but also for the greater recovery of nutrients in cheese. There was a greater recovery of protein with the acid/heat Paneer procedure than the rennet Tosella/Schiz procedure, but we found a species × cheese type interaction for fresh cheese yield. The interaction was related mainly to the higher water retained in the Tosella/Schiz curd rather than to total solids. This led also to greater cooking weight-loss compared with Paneer. The qualitative traits of cheese were highly affected by griddling. Future research on the sensorial perception of cooked cheeses from the two major dairy species is needed to predict consumer response.